Analysis of The Role of Tiktok Social Media as A Mediation Variable on Influence Review Influencer, Endorsement, and Brand Image on The Decision To Purchase The Originote Products In The Millennial Generation - Putu Ayu Candra Jagat Sriastiti; Luh Putu Mahyuni (Pelopor Publikasi Akademika, 2024)
Social media currently plays an important role in all current activities. The use of social media is currently popular among the Millennial Generation. Tiktok has become a popular social media because it has a different appeal than other social media. This study aims to analyze the role of Tiktok social media as a mediating variable in the influence of influencer reviews, endorsements, and brand image on purchasing decisions for The Originote products in the millennial generation. The population in this study was the community of Tiktok Social Media users in Bali Province. Determination of sample size in this study used the Hair formula with a sample size of 138 samples. The data used came from primary data with quantitative data types. Data collection techniques with questionnaires. Data analysis techniques using Structural Equation Modeling (SEM). The results of the analysis show that influencer reviews, endorsements and brand image have a positive effect on purchasing decisions. Social media is able to positively and significantly mediate the influence of influencer reviews, endorsements and brand image on purchasing decisions. The interaction of influencer reviews, endorsements and brand image influences the millennial generation, thus creating a purchasing decision for The Originote mediated by the influence of Tiktok social media.